Grammatical and semantic features of some English words and idioms denoting happiness - the feeling of great pleasure - Lam, Nguyen Thi Van (VNU Journal of Foreign Studies; Vol 25 No 3, 2009)
Abstract. This article is intended for the discussion of the lexemes denoting the feeling of great pleasure sub-classified into four groups of adjectives (‘delighted’, ‘elated’, and ‘jubilant’); nouns  (‘bliss’, ‘ecstasy’, ‘euphoria’, ‘glee’, ‘joy’, and ‘rapture’); verbs (‘exult’ and ‘rejoice’); and idioms (‘walk on air’, ‘in seventh heaven’, ‘on cloud nine’, ‘on top of the world’, ‘over the moon’ and ‘thrilled to bits’). They are dealt with in respect of their grammatical features including the syntactic functions and morphology, and their semantic structures including lexical meaning, synonyms, collocational range, words and idioms of which the word denoting the feeling is a constituent. Some suggestions in the teaching and learning of as well as in the translation concerned with the lexemes are finally provided.